(3GdJfXje GdbGfhfj dYfGUQ GdedcjI GdJLGQjI h GdUfGYjI (B:s (3aj VhA CMcGe GJaGbjI GdJQHS h bGfhf GdedcjI GdacQjI Qbe (B82 (3dSfI (B2002 /s - (3GdfLGQ, eMeO eMSf GHQGgjes ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2005)
(3GKQ faGP GdGJaGbjI Ydi Mbhb GdedcjI GdacQjI GdJbdjOjI h gPG ef NdGd hGbY HQGAGJ GdGNJQGY Hjf GJaGbjI JQHS h bGfhf MeGjI GdedcjI GdacQjI h YfGUQ GdedcjI GdJLGQjI GdUfGYjI h GJaGbjI GdJQHS(B, (3cPdc GKQ GdGJaGbjI Ydi Mbhb GdedcjI GdacQjI GdeSJMOKI h gPG ef NdGd GdJhSY aj fWGb GdMeGjI HehLH GdbhGYO GdbGfhfjI GdJbdjOjI h GdMeGjI GdbGfhfjI ddeYGQa GdafjI(B.s
Keywords: (3GdJfXje GdbGfhfjs; (3GdedcjI GdJLGQjIs